2017
DOI: 10.18632/oncotarget.14440
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes as mediators of platinum resistance in ovarian cancer

Abstract: Exosomes have been implicated in the cell-cell transfer of oncogenic proteins and genetic material. We speculated this may be one mechanism by which an intrinsically platinum-resistant population of epithelial ovarian cancer (EOC) cells imparts its influence on surrounding tumor cells. To explore this possibility we utilized a platinum-sensitive cell line, A2780 and exosomes derived from its resistant subclones, and an unselected, platinum-resistant EOC line, OVCAR10. A2780 cells demonstrate a ~2-fold increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 105 publications
3
82
0
Order By: Relevance
“…Thus, we hypothesized that chemotherapy alters sEV cargo, endowing it with robust neurite outgrowth activity. To test this, we turned to a previously generated set of isogenic cell lines in which the parental cell line (A2780) is platinum sensitive, while two independently derived lines (C30, CP-70) are platinum resistant [55, 56]. Purified sEVs from these cell lines express EV markers (Figure 8F); equal amounts were tested on PC12 cells as previously described (Figures 3 & Supplemental 3) [18, 19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we hypothesized that chemotherapy alters sEV cargo, endowing it with robust neurite outgrowth activity. To test this, we turned to a previously generated set of isogenic cell lines in which the parental cell line (A2780) is platinum sensitive, while two independently derived lines (C30, CP-70) are platinum resistant [55, 56]. Purified sEVs from these cell lines express EV markers (Figure 8F); equal amounts were tested on PC12 cells as previously described (Figures 3 & Supplemental 3) [18, 19].…”
Section: Resultsmentioning
confidence: 99%
“…These findings together with our data suggest that chemotherapy modulates sEV cargo such that robust innervation of residual disease ensues that may ultimately contributes to platinum-resistant recurrent disease. Changes in sEV cargo induced by chemotherapeutic agents have been previously documented and support a bystander effect of chemotherapy on sEVs that ultimately contributes to disease progression [55, 88, 89].…”
Section: Discussionmentioning
confidence: 99%
“…70 A2780, a platinum-sensitive epithelial ovarian cancer (EOC) cell line, displays significantly increased viability upon chemotherapy when pre-exposed to platinum-resistant EOC cell derived EVs, a process accompanied by prominent EMT in A2780 that is caused by EVs from resistant cells. 71 The data revealed one of the major pathways that allow the transfer of treatment resistance between EOC cells.…”
Section: Cell Originmentioning
confidence: 98%
“…EV‐delivered miR‐155 confers gemcitabine chemoresistance to pancreatic cancer cells by downregulating deoxycytidine kinase (DCK, a gemcitabine‐metabolizing kinase), while upregulating superoxide dismutase 2 (SOD2) and catalase (CAT, a reactive oxygen species detoxifying kinase), implying a novel EV‐mediated mechanism of acquired chemoresistance . A2780, a platinum‐sensitive epithelial ovarian cancer (EOC) cell line, displays significantly increased viability upon chemotherapy when pre‐exposed to platinum‐resistant EOC cell derived EVs, a process accompanied by prominent EMT in A2780 that is caused by EVs from resistant cells . The data revealed one of the major pathways that allow the transfer of treatment resistance between EOC cells.…”
Section: Therapeutic Resistance Can Be Conferred By Evs Of Stromal Cementioning
confidence: 99%
“…Recent data revealed that SMAD4 mutations and up‐regulation of miR‐21 perpetuate an EMT phenotype in ovarian cancer cells and enhance chemoresistance profile by exosomal exchange. This mechanism provides a novel insight as to how tumor‐derived exosomal transfer enhances EMT in response to chemotherapy (Crow et al, ). In contrast, prostate cancer cell–derived exosomes, including oncogenic miR‐125b, miR‐130b, and miR‐155, can influence neoplastic reprogramming and tumor progression by inducing MET of mesenchymal stem cells (MSCs) (Abd Elmageed et al, ).…”
Section: Introductionmentioning
confidence: 99%